Pengaruh Frekuensi Pemberian Pakan terhadap Konsumsi Pakan, Pertambahan Berat Badan Harian dan Feed Conversion Ratio pada Ayam Ras Pedaging - Samlawi Samlawi; Rastosari A; Patria C A (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2018)
The purpose of this study was to determine the effect of feeding frequency on feed intake, average daily gain (ADG) and Feed Conversion Ratio (FCR) in broiler. The research method used in this study is the experimental method, which is the type of research used to find the effect of certain treatment against others in controlled conditions. This research was conducted on poultry breeding farm at Company Farm. Method of data collection used in this research using instrument that is observation sheet to get feed intake, average daily gain, and FCR. The data obtained were analyzed by using independent sample t-test test with SPSS version 17. 00 software. The feeding method did not affect feed intake, ADG and FCR. The average intake of chicken feed maintained by using the method of feeding 2 times was 59.33 g lower than using the method of feeding 3 times, namely 59.41 g. The ADG by feeding method 2 times was 45.29 g, while by feeding method 3 times was 46,21 g. The value of FCR method of feeding 3 times is 1,286, meaning that to produce 1 kg of meat requires 1,286 kg of feed. While the value of chicken FCR on feeding method 2 times is 1,311, that means to produce 1 kg of meat requires as much as 1,311 kg of feed. Keywords: Average Daily Gain, Broiler, Feed Intake, Feed Conversion Ratio